A Rare Presentation of HIV-Negative Plasmablastic Lymphoma: A Diagnostic Dilemma - Alaina J. Kessler; Bridget K. Marcellino; Scot A. Niglio; Bruce E. Petersen; Adriana K. Malone (Case Reports in Hematology)
Plasmablastic lymphoma (PBL) and plasmablastic plasma cell myeloma (PCM) have many overlapping characteristics. Clinical correlation can help make the distinction between the two entities. Human immunodeficiency virus- (HIV-) negative PBL is a rare disease, making the diagnosis more challenging. While there is no standard of care for PBL, current recommendations include dose-adjusted EPOCH (etoposide, vincristine, doxorubicin, cyclophosphamide, and prednisone), with or without bortezomib. We report an aggressive case of HIV-negative plasmablastic lymphoma and discuss the challenge in establishing a diagnosis. We review the literature regarding this disease and current recommendations for treatment.